Educational Policy of Kazakhstan in the Context of Youth Migration - V. Yu. Ledeneva; O. V. Lomakina; A. M. Dzhunusov; B. T. Begasilov (Высшее образование в России)
Educational migration largely determines the dynamics and nature of the country’s economic development and is viewed as a factor in increasing the country’s competitiveness and building up human capital. In this context, an increasing problem for Kazakhstan is the regulation of educational migration in the context of fierce competition in the international market of educational services.A review of publications showed that the issues of regulating educational migration from Kazakhstan are not widely covered in scientific discourse. There are practically no scientific works on the political and legal aspects of youth migration. But even if there are such publications, then, as a rule, they are devoted to the analysis of youth migration in Central Asia in general. The relevance of the study is determined by the gradual expansion of educational contacts of Kazakhstan with other countries and the need to identify the competitive advantages of foreign educational systems over the national higher education system of Kazakhstan.The purpose of the article is to consider the main motives, causes and consequences of educational migration from Kazakhstan, to analyze the activities of the authorities and ways of regulating youth migration, develop new effective methods for regulating external migration processes and provide recommendations on minimizing the risks associated with the outflow of young people from the country.In order to identify the main trends and development of educational migration from Kazakhstan, the study was carried out on the basis of collecting information through a questionnaire, as well as its detailed processing and content analysis. Kazakhstani students studying in Russia took part in the survey. The sample consisted of 183 people.As a result of the study, the main reasons for the dynamic growth of educational migration from Kazakhstan were identified, such as the high quality of education abroad, the availability of education in Russian universities, comfortable learning and living conditions for Kazakhstanis, etc. Recommendations for authorities on regulating educational migration that can be used by other countries facing the problem of the outflow of youth abroad in order to receive education. The results of this work can be useful to scientists and teachers engaged in research on various aspects of educational migration in Kazakhstan.